2008
DOI: 10.4238/vol7-4gmr499
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Nelore cattle: a melting pot unfolded by molecular genetics

Abstract: ABStrACt. The aim of the present article was to study the population structure and genetic diversity of Nelore cattle and genetic relationships between Nelore and different taurine and zebu breeds raised in Brazil. DNA polymorphism analysis was carried out with 1976 animals of 16 zebu, taurine and synthetic breeds raised in Brazil. A higher genetic differentiation was observed in taurine than in zebu cattle. Gene flow was intense between the different zebu populations. Genetic affinity analysis within the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Nonetheless, large-scaled commercial production systems were established only after the importation of zebuine breeds from India in the late 19th and 20th centuries (Cervini et al, 2006). Adapted to the tropical ecological settings found in Brazil, zebuine cattle rapidly became prominent in most herds and contributed to the development of new American breeds such as Nelore, Tabapuã, Indubrazil, and Girolando (Dani et al, 2008). Other conspicuous commercial breeds raised in Brazil, such as Brahman and Senepol, were also formed during the last century, although in other countries of the American continent (Novoa and Usaquén, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, large-scaled commercial production systems were established only after the importation of zebuine breeds from India in the late 19th and 20th centuries (Cervini et al, 2006). Adapted to the tropical ecological settings found in Brazil, zebuine cattle rapidly became prominent in most herds and contributed to the development of new American breeds such as Nelore, Tabapuã, Indubrazil, and Girolando (Dani et al, 2008). Other conspicuous commercial breeds raised in Brazil, such as Brahman and Senepol, were also formed during the last century, although in other countries of the American continent (Novoa and Usaquén, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These animals resulted, in the large part, from absorbing crossbreeding between zebuine bulls imported from different regions of India and local taurine dams (Mariante et al, 1999). Furthermore, Brazilian Creole cattle also contributed to the formation of some American derivatives of zebuine breeds (such as Tabapuã) (Mariante et al, 1999;Dani et al, 2008). It has been shown that Latin American Creole breeds may carry either European-or Africanoriginated taurine DNA (Lirón et al, 2006;Ginja et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations